Uncovering the Role of Chemical and Electronic Structures in Plasmonic Catalysis: The Case of Homolysis of Alkoxyamines; ACS Catalysis; Vol. 13, iss. 5 - Votkina D. E. Darjya Evgenjevna; Petunin P. V. Pavel Vasilievich; Miliutina E. Elena; Trelin A. Andrii; Lyutakov O. Oleksiy; Svorcik V. Vaclav; Audran G. Gerard; Havot J. Jeffrey; Valiev R. R. Rashid Rinatovich; Valiulina L. I. Lenara; Joly J. P. Jean-Patrick; Yamauchi Yu. Yusuke; et al. (2023, 2023)
Title screen